A new analytical protocol for the determination of cadmium in sunflower oil samples: Micro-sampling cold vapor generation-atomic absorption spectrometry after spraying based microextraction method - Bodur, Sueleyman; Tutar, Bahar Karademir; Bodur, Sezin Erarpat; Tutar, Omer Faruk; Bakirdere, Sezgin (ELSEVIER SCI LTD, 2025)
This study presents a new analytical method for the determination of cadmium at trace levels in sunflower oil using vortex assisted reverse phase-spraying-based fine droplet formation liquid phase microextraction method (VA-RP-SFDF-LPME), followed by micro-sampling cold vapor generation-atomic absorption spectrometry (CVGAAS) system. Micro-sampling - gas liquid separator unit was custom designed in our laboratory to transfer the analyte-rich phase to the CVG-AAS system. Under the optimum conditions of the VA-RP-SFDF-LPME-micro-sampling-CVG-AAS method, the limit of detection, limit of quantitation and working dynamic range were found as 0.13 mu g/kg, 0.44 mu g/kg and 0.53-10.39 mu g/kg, respectively. The percent recovery results for the spiked sunflower samples ranged from 87.6 % to 101.1 %. The greenness and practicality of developed method were assessed using AGREEprep and BAGI tools, which scored 0.27 and 62.5 points, respectively. This method offers an effective and environmentally friendly solution for detecting cadmium contamination in edible oil samples.
Keywords: Cadmium; Sunflower oil; Micro-sampling cold vapor generation; Atomic absorption spectrometry; Spraying based microextraction; HEAVY-METALS; HYDRIDE GENERATION; TRACE-ELEMENT; EDIBLE OILS; OLIVE OILS; REDUCTION; NITRATE; EXTRACTION; NITRITE; ZINC; Chemistry; Food Science & Technology; Nutrition & Dietetics